In vivo study for the discrimination of cancerous and normal skin using fibre probe-based Raman spectroscopy - Schleusener, Johannes; Gluszczynska, Patrycja; Reble, Carina; Gersonde, Ingo; Helfmann, Jürgen; Fluhr, Joachim W.; Lademann, Jürgen; Röwert-Huber, Joachim; Patzelt, Alexa; Meinke, Martina C. (Experimental dermatology, 2015)
Raman spectroscopy has proved its capability as an objective, non‐invasive tool for the detection of various melanoma and non‐melanoma skin cancers (NMSC) in a number of studies. Most publications are based on a Raman microspectroscopic ex vivo approach. In this in vivo clinical evaluation, we apply Raman spectroscopy using a fibre‐coupled probe that allows access to a multitude of affected body sites. The probe design is optimized for epithelial sensitivity, whereby a large part of the detected signal originates from within the epidermal layer's depth down to the basal membrane where early stages of skin cancer develop. Data analysis was performed on measurements of 104 subjects scheduled for excision of lesions suspected of being malignant melanoma (MM) (n = 36), basal cell carcinoma (BCC) (n = 39) and squamous cell carcinoma (SCC) (n = 29). NMSC were discriminated from normal skin with a balanced accuracy of 73% (BCC) and 85% (SCC) using partial least squares discriminant analysis (PLS‐DA). Discriminating MM and pigmented nevi (PN) resulted in a balanced accuracy of 91%. These results lie within the range of comparable in vivo studies and the accuracies achieved by trained dermatologists using dermoscopy. Discrimination proved to be unsuccessful between cancerous lesions and suspicious lesions that had been histopathologically verified as benign by dermoscopy.